2010
DOI: 10.1007/s12029-010-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies for Locoregional Recurrence in Early-Stage Gastric Cancer: Retrospective Analysis and Comprehensive Literature Review

Abstract: While acknowledging the limitations of this study, including the small sample size and the short follow-up period, it appears clear that oncologic treatment is possible for EGC recurrence, particularly, in patients with isolated relapse. Guideline updates should differentiate between management strategies suitable for recurrence occurring in early versus advanced initial cancer stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Many studies have shown that gene expression signatures can classify tumors into intrinsic subtypes and predict the survival of GC patients [26] . Several genomic studies also show that gene expression profiling can predict patients with a high risk for recurrence and thus can potentially improve clinical practice [42–44] . Now it is evident that gene expression techniques may significantly improve our ability to predict the risk of recurrence and to tailor the treatment for each individual gastric cancer patient.…”
Section: Molecular Prognosis Of Gcmentioning
confidence: 99%
“…Many studies have shown that gene expression signatures can classify tumors into intrinsic subtypes and predict the survival of GC patients [26] . Several genomic studies also show that gene expression profiling can predict patients with a high risk for recurrence and thus can potentially improve clinical practice [42–44] . Now it is evident that gene expression techniques may significantly improve our ability to predict the risk of recurrence and to tailor the treatment for each individual gastric cancer patient.…”
Section: Molecular Prognosis Of Gcmentioning
confidence: 99%
“…In early gastric cancer, the rate of recurrence after gastrectomy is reported to vary from 1.3 to 12.2%. Median time to recurrence is 16 months, and hematogenous spread is probably the most common pattern of recurrence [12]. …”
Section: Reasons For Follow-upmentioning
confidence: 99%
“…Recurrences were classified as either locoregional, distant, or peritoneal, and as with previous reports, distant recurrences, though rare, were the predominant recurrence in our cohort of node‐negative early gastric cancer . Patients with lymph node metastasis, perhaps the most important predictor for recurrence in gastric cancer , were purposely excluded from this study.…”
Section: Discussionmentioning
confidence: 92%
“…The proportion of early gastric cancer (T1‐2) has increased in recent years , possibly due to a combination of increased screening and improved diagnostic techniques. Early gastric cancer (T1‐2N0) rarely recurs following curative resection, and the current NCCN Gastric Cancer Guidelines do not recommend adjuvant treatment for this subgroup of gastric cancer patients .…”
Section: Introductionmentioning
confidence: 99%